Interpersonal and systemic factors in initiating, developing and maintaining collaborations between European neurosurgical departments and institutions in low-resources settings: A qualitative study - Nicolò Marchesini; Vicki M. Butenschoen; Andreas K. Demetriades; Said Idrissa Ahmada; Fazlul Hoque; Thomas Kapapa; Patrick D. Kamalo; Pablo González-López; Rupavathana Mahesperan; Ondra Petr; Wilco Peul; Nicephorus Boniface Rutabasibwa; et al. (Brain and Spine)
Introduction: Neurosurgical care in low- and middle-income countries faces persistent challenges, including insufficient infrastructure, lack of trained surgeons, and limited access to sustainable training programs. Collaborative initiatives with high-income countries aim to address these gaps. However, in-depth studies of European-led partnerships and the interpersonal and systemic factors underpinning their success remain limited. Research question: What are the most salient interpersonal and systemic factors relevant to the a) initiation, b) development, and c) maintenance of effective and sustainable collaborations between European neurosurgical departments and institutions in resource-limited settings? Material and methods: We conducted a prospective qualitative study using semi-structured interviews with fourteen matched neurosurgeons—seven from European centers and seven from LMIC institutions—engaged in such collaborations. Data were collected virtually between May and August 2024. Transcripts were analyzed thematically to identify major themes, which were coded and categorized. Results: Twelve themes emerged, grouped into three stages: a) initiation: trust and personal connections, systematic planning and foundations, local context and needs, institutional and government support; b) development: capacity building and skills development, academic and research growth, challenges to development and adaptation; c) maintenance: sustainability and independence, resources and logistical support, communication and continuous commitment, outcome measures and accountability, and challenges to maintenance and advices for continuity. Discussion and conclusions: Findings highlight recurring interpersonal and systemic dynamics central to successful long-term partnerships. This study provides context-specific, real-world insights into their practical execution. Future efforts should focus on developing targeted recommendations to strengthen global neurosurgical collaborations and address inequities in access to care.